Evaluation & characterization of biodegradable polymer - Loo, Jason Zi Shun (2019)
Biodegradable plastics are gaining popularity in recent years as the general public have been more aware of what plastics have done to Earth. To deal with such issues, companies around the world are opting for the use of biodegradable plastics. These plastics are usually composed of starch and bioplastics that are biodegradable by nature. This report presents the identification and characterization of a biodegradable polymer bag by exposing it under various environmental conditions such as heat, water and soil. The experiments conducted includes fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimeter (DSC) tensile tests and scanning electron microscope (SEM). The results gotten from FTIR spectrum revealed that the biodegradable polymer bags were made of polylactic acid (PLA) and well as tapioca starch. By exposing these samples to heat and water, the moisture content within the samples changed. The physical and mechanical properties changed according to the amount of moisture present in the sample whereby higher moisture content led to lower ultimate tensile strength, Young’s modulus and higher tensile strain at break while lower moisture content yield the opposite in these properties. The increase in moisture content also decreases glass transition temperature while increasing melting temperature. Likewise, changes were observed for samples that were buried in soil. Soil degradation increase the UTS and Young’s while decreasing tensile strain, however, these results were the opposite from previous studies’ results. As the amount of time for experiment and soil differs from past studies, it cannot be concluded if the results obtained were accurate. To conclude, it is safe to assume that the results obtained from the studies on the effects of moisture is accurate and that the biodegradable polymer bag should not be used in either high or low moisture content. The normal condition bag provides the best properties for usage.